Animal Welfare and Farmers' Satisfaction in Small-Scale Dairy Farms in the Eastern Alps: A “One Welfare” Approach - Spigarelli, Chiara; Berton, Marco; Corazzin, Mirco; Gallo, Luigi; Pinterits, Sabine; Ramanzin, Maurizio; Ressi, Wolfgang; Sturaro, Enrico; Zuliani, Anna; Bovolenta, Stefano (Frontiers in Veterinary Science, 2021)
The multidimensional concept of animal welfare includes physical health, good emotional state and appropriate behavior of the animals. The most recent methods for its assessment are inspired by the Welfare Quality, a project compiling animal-, resource- and management-based measures. Recently, animal welfare assessment has also considered the human factor in a so called “One Welfare” approach. The One Welfare framework highlights the interconnections between animal welfare, human well-being and the environment. The concept seems to fit particularly well to mountain areas where the relationship between human, animals and the environment is stronger. In such disadvantaged areas farmers’ well-being plays a key role in maintaining livestock farming profitable and sustainable. This study aims to investigate the relationship between farmers’ satisfaction, animal welfare outcomes and the overall farm performance in 69 small-scale dairy farms in the Eastern Alps. Animal welfare assessment consisted of animal-based measures and was performed using the methodology proposed by EFSA for this type of farms. Moreover, the farmers were interviewed to retrieve data on farm characteristics and on their level of satisfaction towards: workload, land organization, relationship with agricultural/non-agricultural community and the future of local agriculture. The results showed that good animal welfare can be obtained in mountain farming system. Clinical indicators showed a low prevalence of diseases and of very lean cows as opposed to integument alterations. Workload is not perceived as a problem in traditional farms (i.e. tie-stall and with no participation in quality certification schemes). Animal welfare is higher in those farms were farmers have a positive engagement with both the agricultural and non-agricultural community and in those farms where farmers are satisfied with their land organization. A One Welfare approach could be applied at a larger scale to fully understand links between animal and human well- being in mountain areas.